Erratum: A Historical Overview of Protected Agriculture in the State of Sinaloa, Mexico: Implications for Improving Rural Prosperity - JIAEE Editors (Journal of International Agricultural and Extension Education, 2024)
Correction: The DOI of the article "Flores, L. A., & Edwards, C. M. (2019). A Historical Overview of Protected Agriculture in the State of Sinaloa, Mexico: Implications for Improving Rural Prosperity. Journal of International Agricultural and Extension Education, 26(3), 7-26” was incorrect as published. The correct DOI is: 10.5191//jiaee.2019.26301